2007
DOI: 10.1088/0957-0233/18/2/s23
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on nanoparticle sizes under the APEC technology cooperative framework

Abstract: Despite the fact that there exist several techniques capable of characterizing nanoparticle sizes, their measurement results from the same sample often deviate from each other by an amount that is considered significant on the nanometre scale. In the absence of international standards, or worldwide recognized protocols dealing with nanoparticle characterization, an APEC-led preliminary interlaboratory comparison on nanoparticle size characterization was carried out among ten laboratories from six member econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…4a are smaller than the DLS measurement but a direct comparison between the two techniques is complicated by factors such as sample size, sensitivity to hydrodynamic conditions in DLS measurements, etc. [40,41]. The GNP-SSPLGA are fairly welldispersed as isolated particles in the sample deposited at high pH (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…4a are smaller than the DLS measurement but a direct comparison between the two techniques is complicated by factors such as sample size, sensitivity to hydrodynamic conditions in DLS measurements, etc. [40,41]. The GNP-SSPLGA are fairly welldispersed as isolated particles in the sample deposited at high pH (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…To date there have been few measurements of manufactured nanoparticles in natural waters or soils because of the extreme difficulty in detecting those at environmentally relevant concentrations [20,21] while avoiding the potential interference of natural nanoparticles frequently present in environmental samples [22]. It has been reported that the average size and size distribution of nanoparticles can significantly vary when comparing results from different techniques [23]. Each technique is not without limitations and, therefore inaccurate predictions of material properties and structure can result.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the most challenging steps in TEM is preparation of a sample sufficiently thin to allow the electrons to pass through. (108,110,111) More complex food samples are embedded in resin and cut into 15-90 nm thin sections by means of ultramicrotomy or focused ion beam (FIB) milling. Liquid samples are prepared as resin-embedded specimens without sectioning by adding a water-soluble melamine resin (e.g.…”
Section: Sampling and Sample Preparation For Electron-microscopy Analmentioning
confidence: 99%